Incidence of patients with non-cystic fibrosis bronchiectasis in Germany – A healthcare insurance claims data analysis. (May 2019) - Diel, Roland; Ewig, Santiago; Blaas, Stefan; Jacob, Christian; Juelich, Fabian; Korfmann, Gisela; Sohrab, Sebastian; Sutharsan, Sivagurunathan; Rademacher, Jessica
Abstract: Background: Incidence and prevalence of patients with non-cystic fibrosis bronchiectasis (NCFB) appear to be increasing worldwide but supporting epidemiological data are scarce. This study assesses the incidence of NCFB patients in Germany in 2013 and analyzes comorbidities and basic patterns of resource use. Methods: A representative sample of 3.988.648 anonymized persons covered by German public statutory health insurances was used to identify incident patients with NCFB in 2013. Results: After extrapolation to the general population of the 728 patients found in the reference insurance database, we estimate that a total of 17, 095 NCFB patients were newly diagnosed across the country in 2013 as having NCFB. This corresponds to an incidence of 21.23 per 100.000 inhabitants. The majority of NCFB patients (98.4%) was at least 18 years old, and 52.7% of the NCFB patients were male. Trend analysis shows a rise of NCFB incidence in Germany from 2011 through 2013. COPD (41.4%), asthma (32.8%) and gastroesophageal reflux (18.3%) were the most frequent predisposing conditions. Coronary heart disease was observed in more than one quarter of NCFB patients (28.2%). 58.4% of the NCFB outpatients received antiobstructive inhalative medication. Of the adult NCFB patients, 51.6% were prescribed antibiotics to treat NCFB by settled doctors (outpatient treatment); 51.5% of those patients were males. The peak of antibiotic treatment was observed in the 75–79 age group for males and 70–74 and 75–79 years for females. The majority of diagnosed patients (54.1%) received at least two prescriptions during 2013. Bacterial pathogens were coded for a total of 10.7% of NCFB patients, while Pseudomonas aeruginosa was only documented in 2.3%. Among those diagnosed in 2013, 8.0% of the adult NCFB patients who received antibiotic treatment had to be hospitalized. Conclusions: Although hospital admissions due to exacerbation in the first year of diagnosing NCFB are not rare, outpatient burden and costs must also be considered a major part of care. Given the increasing recognition of NCFB, a better understanding of the economic burden of the disease is required, with a view towards improving patient management. For this, more detailed, prospective studies are needed. Highlights: The manuscript shows the first results for the incidence of bronchiectasis in Germany. COPD, asthma and gastroesophageal reflux were the most frequent predisposing conditions. The peak of antibiotic treatment was observed in the 75–79 age group for males and 70–74 and 75–79 years for females. The majority of diagnosed patients received at least two prescriptions during 2013.